Eosinophilic Esophagitis is a Late Manifestation of the Allergic March - Hill, David A. (J Allergy Clin Immunol Pract, 2018)
BACKGROUND: The allergic march describes the natural history of allergic conditions as they develop during childhood. Eosinophilic esophagitis (EoE) is a chronic allergic inflammatory disease that can be triggered by specific foods. Despite its allergic pathophysiology, the epidemiologic relationship between EoE and established members of the allergic march is unknown. OBJECTIVE: We sought to determine whether EoE meets epidemiologic criteria for being considered a member of the allergic march. METHODS: Utilizing a primary care birth cohort of 130,435 children, we determined the natural histories of atopic dermatitis (AD), IgE-mediated food allergy (IgE-FA), asthma, EoE, and allergic rhinitis (AR) in individual patients. We then performed case-control analyses to establish the extent that existing allergic conditions influence the rate of subsequent EoE diagnosis. RESULTS: 139 children developed EoE during the observation period (prevalence of 0.11%). Peak age of EoE diagnosis was 2.6-years, as compared with 0.3-years, 1-year, 1.1-years, and 2.1-years for AD, IgE-FA, asthma, and AR, respectively. Presence of AD (hazard ratio [HR] 3.2, 95% confidence interval [CI] 2.2–4.6), IgE-FA (HR 9.1, 95% CI 6.5–12.6), and asthma (HR 1.9, 95% CI 1.3–2.7) were independently and cumulatively associated with subsequent EoE diagnosis. Presence of AR was associated with subsequent EoE diagnosis (HR 2.8, 95% CI 2.0–3.9), and presence of EoE was associated with subsequent AR diagnosis (HR 2.5, 95% CI 1.7–3.5). CONCLUSION: Allergic comorbidities are positively associated with EoE diagnosis. Together, our findings suggest that EoE is a late manifestation of the allergic march.